Isochromatic photoelasticity fringe patterns of PMMA in various shapes and stress applications - Y. Manjit (2018)
© 2018 SPIE. The research focuses on isochromatic photoelastic fringe patterns in solid materials by using reflection mode in dark field polariscope. The optical setup consists of light source, polarizers, quarter wave plates, 577 nm optical pass filter, compensator and digital camera system. The fringe patterns were produced on the sample and fractional / integer number of fringe order was observed using Babinet compensator and digital camera system. The samples were circular and rectangular shape of PMMA coated with silver spray and compressed by hydraulic system at the top and the bottom. The results of the isochromatic fringe pattern were analyzed in horizontal and vertical positions. It was found that force and the number of isochromatic photoelastic fringe order depended on shape of sample, which reflects stress distribution behavior.